PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA BERBASIS WEB - Muhammad Syahril Harahap; Rahmad Fauzi (Jurnal Education and Development, 2017)
Learning to use the module has several characteristics, which are self instruction, recognition of individual differences, includes learning objectives / competence, their associations, structures and uurutan knowledge, the use of a variety of multi-media, the active participation of students, their reinforcement directly to the response of the students, their evaluation of the student mastery over the learning results. In developing the modules need to pay attention to the techniques and components required, such as: components of a review of subjects, introduction, learning activities, exercises, summaries, formative tests and answer keys formative tests and follow-up. While the technique of developing modules include strarting from scratch, repackaging information, and compilation. Utilization of the module in the learning process sector in the class can be done on individual learning systems and classical. paper entitled Development of Web-Based Learning Module aims: 1) to produce web-based learning modules, 2) determine students' attitude towards web-based learning modules, 3) Knowing student results after participating in learning to use the web-based learning modules. It can be concluded that learning to use the learning module further web-based social statistics have been classified in either category even very good. Competency develop teaching materials especially modules need to be owned by teachers, considering the teaching materials will further streamline and mengefiensiensikan learning process. Besides, it also has an important role of teaching materials for teachers and students, the learning is done individually, and classical groups.